Explosive Decay of Emulsion Drops Based on Water and Oil Products under Conditions of High-Temperature Purification of Liquids; Doklady Physics; Vol. 63, iss. 11 - Nakoryakov V. E. Vladimir Eliferjevich; Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2018, 2018)
Title screen